Is tracheostomy suitable for securing airway after facial firearm injuries? - Oksan, Derinoz (Second Affiliated Hospital of Zhejiang University School of Medicine, 2011)
BACKGROUND: Head and neck region have many vital structures, and facial firearm injuries (FFIs) more likely lead to life-threatening situations than other body injuies. These injuries have high potential of airway compromise associated with significant morbidity and mortality. METHODS: We describe an 11-year-old boy who had received tracheostomy after a FFI complicated with pneumothorax and subcutaneous emphysema 8 hours after the procedure. The patient was treated at the Department of Emergency and Critical Care, Gazi University School of Medicine, Turkey. RESULTS: The patient was discharged without any complications from the Critical Care Unit after treatment for five days. CONCLUSIONS: Airway management is of utmost importance in resuscitation of FFI, but it is always difficult to secure via the orotracheal route due to the deformed facial structures. Tracheostomy is an option for airway management in FFI affecting head and neck region. However, tracheostomy may be associated with life-threatening complications, which should be closely monitored with early intervention.